Invariant Charge Carrier Dynamics Using a Non-Planar Non-Fullerene Acceptor across Multiple Processing Solvents - Gonev, Hristo Ivov; Jones, Elena; Chang, Chia-Yu; Ie, Yutaka; Chatterjee, Shreyam; Clarke, Tracey M. (Journal of physical chemistry. C, 2024)
Conventional non-fullerene acceptors (NFAs) typically have planar structures that can enable improved electron mobility and produce more efficient organic photovoltaic devices. A relatively simple A-D-A′-D-A type NFA specifically designed to match with poly(3-hexylthiophene-2,5-diyl) (P3HT) for green-absorbing agrivoltaic applications has been examined using a variety of techniques: microsecond transient absorption spectroscopy, atomic force microscopy, and photoluminescence. Relatively invariant charge carrier decay dynamics are observed in the blend films across a variety of processing solvents. Raman spectroscopy in conjunction with computational studies reveals that this NFA is non-planar and that multiple conformations are present in films, while preserving the crystalline nature of P3HT. The non-planarity of the NFA therefore creates a dispersive acceptor environment, irrespective of processing solvent, and this leads to the observed relative invariance in charge carrier decay dynamics and high tolerance to morphological variation. The findings presented in this work highlight the potential of non-planar materials as acceptors in organic photovoltaic devices.